Global analysis of a delayed vector-bias model for malariatransmission with incubation period in mosquitoes - Cruz Vargas-De-León (Mathematical Biosciences and Engineering)
A delayed vector-bias model for malaria transmission withincubation period in mosquitoes is studied. The delay $τ$corresponds to the time necessary for a latently infected vectorto become an infectious vector. We prove that the global stabilityis completely determined by the threshold parameter, $R_0(τ)$.If $R_0(τ)≤1$, the disease-free equilibrium is globallyasymptotically stable. If $R_0(τ)>1$ a uniqueendemic equilibrium exists and is globally asymptotically stable.We apply our results to Ross-MacDonald malaria models with anincubation period (extrinsic or intrinsic).